CHECHNIA: PROBLEMS OF SOCIOECONOMIC REVIVAL AND DEVELOPMENT PROSPECTS - MAGOMADOV, Mukhtar (CENTRAL ASIA AND THE CAUCASUS, 2004)
In the early 1990s, Chechnia had a most powerful production, technological and socioeconomic potential. It had a unique educational, scientific and technical conglomerate for the production,processing and use of oil and gas, which was of great importance for world science and practice. In 1991, oil production in the republic was around 5m tonnes (in 1972, the figure was 21.6m, and in 2002, 1.5m tonnes), refining was close to 19m tonnes, and employment in the oil sector (including in related areas of activity) was around 200,000 people, dropping to less than 3,000 in 2002. In addition, the republic had more than 20 enterprises operating in other industries and a powerful Agroindustrial complex. There was an effective system for training highly skilled workers, engineers and technicians built up in the preceding decades, an intensively developing social sphere, science, ed-ucation, health care, culture, etc. But in the early 1990s the situation in Chechnia, just as in virtually all other regions of the former U.S.S.R., was already affected by the early results of the reforms launched by Mikhail Gorbachev in the mid-1980s and known as perestroika. Whereas its political prerequisites were connected with the necessity of changing the sociopolitical system of the Soviet Union, its socioeconomic prerequisites were conditioned by the imperative need to go over from the administrative-command system of economic governance to market mechanisms. These processes engendered a number of negative phenomena: a deep economic crisis; a crisis of the outgoing administrative system and formation of a new economic mechanism; a political crisis, largely caused by the disintegration of the Communist Party of the U.S.S.R. and transfer of power to the Soviets (far from voluntarily); and an ideological crisis connected with the difficulties of shedding old dog-mas, with the inertia of society’s political consciousness, and with the collapse of faith in the social jus-tice of the Soviet state.